Underlying Cryptococcal Diseases and the Correlation With Serum Cryptococcal Antigen Titers in Hospitalized HIV-Infected Patients Screened Positive for Cryptococcal Antigenemia - Xu, Miaomiao (Front Cell Infect Microbiol, 2020)
Background: The prevalence of different underlying cryptococcal diseases in human immunodeficiency virus (HIV)-infected patients screened positive for cryptococcal antigenemia and the association between cryptococcal diseases and serum cryptococcal antigen (CrAg) titers were understudied. Methods: HIV-infected patients with CD4 < 200 cells/ul, admitted to the second hospital of Nanjing, Nanjing, China, from January 2016 to September 2019, were retrospectively analyzed. Integrated into routine HIV care, all these patients were screened for cryptococcal antigenemia with CrAg lateral flow assay. Positive patients received extensive laboratory and radiological studies to evaluate underlying cryptococcal diseases. Results: A total of 872 HIV inpatients were screened for serum CrAg. The prevalence of cryptococcal antigenemia in the study population was 10.3% (95% CI, 8.3–12.3%), 87.6% of which with cryptococcal antigenemia had clinically cryptococcal diseases. The prevalence of cryptococcal meningitis (CM), cryptococcemia and pulmonary cryptococcosis (PC) in patients with cryptococcal antigenemia were 58.4% (95% CI, 48.0–68.9%), 50.7% (95% CI, 39.1–62.2%), and 68.5% (95% CI, 58.7–78.4%), respectively. The median (range) serum CrAg titers in severe cryptococcal diseases (CM or cryptococcemia), localized PC (without co-existing CM or cryptococcemia) and isolated cryptococcal antigenemia were 1:2560 (1:10–1:2560), 1:20 (1:2–1:320), and 1:5 (1:2–1:320), respectively. Serum CrAg titers ≥1:320 were independently associated with CM (adjusted OR 26.88; 95%CI, 8.36–86.42). Severe cryptococcal diseases were found in all patients with serum CrAg titers ≥1:640. None of the patients with serum CrAg titers ≤ 1:5 had CM. Conclusion: The prevalence of cryptococcal antigenemia was high in HIV inpatients, supporting routine CrAg screening. Clinical cryptococcal diseases, most commonly the PC, existed in the majority of the patients with cryptococcal antigenemia. Since serum CrAg titer is correlated with cryptococcal disease severity, it may possibly guide anti-fungal treatment.